ASA class is associated with early revision and reoperation after total hip arthroplasty: an analysis of the Geneva and Swedish Hip Arthroplasty Registries. (4th July 2019) - Ferguson, Rory J; Silman, Alan J; Combescure, Christophe; Bulow, Erik; Odin, Daniel; Hannouche, Didier; Glyn-Jones, Siôn; Rolfson, Ola; Lübbeke, Anne
Abstract : Background and purpose — Data from several joint replacement registries suggest that the rate of early revision surgery after primary total hip arthroplasty (THA) is increasing. The ASA class, now widely recorded in arthroplasty registries, may predict early revision. We investigated the influence of ASA class on the risk of revision and other reoperation within 3 months and within 5 years of primary THA. Patients and methods — We used data from the Geneva and Swedish Hip Arthroplasty Registries, on primary elective THAs performed in 1996–2016 and 2008–2016, respectively. 5, 319 and 122, 241 THAs were included, respectively. Outcomes were all-cause revision and other reoperations evaluated using Kaplan–Meier survival and Cox regression analyses. Results — Within 3 months after surgery, higher ASA class was associated with greater risk of revision and other reoperation. 3-month cumulative incidences of revision by ASA class I, II, and III–IV respectively, were 0.6%, 0.7%, and 2.3% in Geneva and 0.5%, 0.8%, and 1.6% in Sweden. 3-month cumulative incidences of other reoperation were 0.4%, 0.7%, and 0.9% in Geneva and 0.2%, 0.4%, and 0.7% in Sweden. Adjusted hazard ratios (ASA III–IV vs. I) for revision within 3 months were 2.7 (95% CI 1.2–5.9) in Geneva and 3.3 (CI 2.6–4.0) in Sweden. Interpretation — Assessment of ASA class of patients prior to THA will facilitate risk stratification. Targeted risk-reduction strategies may be appropriate during the very early postoperative period for patients identified as at higher risk. Systematically recording ASA class in arthroplasty registries will permit risk adjustment and facilitate comparison of revision rates internationally.